2022
DOI: 10.3390/ijerph191610170
|View full text |Cite
|
Sign up to set email alerts
|

Quitting Smoking before and after Pregnancy: Study Methods and Baseline Data from a Prospective Cohort Study

Abstract: Smoking during pregnancy and postpartum remains an important public health problem. No known prior study has prospectively examined mutual changes in risk factors and women’s smoking trajectory across pregnancy and postpartum. The objective of this study was to report methods used to implement a prospective cohort (Msgs4Moms), present participant baseline characteristics, and compare our sample characteristics to pregnant women from national birth record data. The cohort study was designed to investigate smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Anxiety, postpartum depression, and negative emotions [18,21] Alcohol consumption [21] Strong cravings for cigarettes (increased nicotine dependence) [21] The absence of assistance from medical professionals [21] Staying in a place where there is smoke [21] Returning to work (colleagues who are smokers) [21] Education and education level [28] The low income [18] Weight gain [35] The few attempts to quit smoking [30,39] The temporary cessation of smoking [30,39] Not being worried about the negative health effects of smoking [39] The significant increase in the number of pregnancies and children [39] The presence of a smoking partner in the home environment [18,21] Smoking before and after childbirth [39] Not wanting another pregnancy [39] The duration of abstinence from smoking [30] the Edinburgh Postnatal Depression Scale at the end of pregnancy can help determine the success of a postpartum smoking relapse prevention intervention 26,30 .…”
Section: Risk Factors For Not Quitting or Resuming Smokingmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety, postpartum depression, and negative emotions [18,21] Alcohol consumption [21] Strong cravings for cigarettes (increased nicotine dependence) [21] The absence of assistance from medical professionals [21] Staying in a place where there is smoke [21] Returning to work (colleagues who are smokers) [21] Education and education level [28] The low income [18] Weight gain [35] The few attempts to quit smoking [30,39] The temporary cessation of smoking [30,39] Not being worried about the negative health effects of smoking [39] The significant increase in the number of pregnancies and children [39] The presence of a smoking partner in the home environment [18,21] Smoking before and after childbirth [39] Not wanting another pregnancy [39] The duration of abstinence from smoking [30] the Edinburgh Postnatal Depression Scale at the end of pregnancy can help determine the success of a postpartum smoking relapse prevention intervention 26,30 .…”
Section: Risk Factors For Not Quitting or Resuming Smokingmentioning
confidence: 99%
“…Some of the studies [18][19][20] identified by this systematic review implement a smoking cessation intervention program during the postpartum period using technology [text messages, emails, smartphone applications, videography, telephone counseling lines for smoking cessation, etc.) in order to facilitate participants and urge them to continue the cessation effort by making the necessary meetings (followup)] or answering their questions from wherever they were.…”
Section: Smoking Cessation Intervention Programs During the Postpartu...mentioning
confidence: 99%
See 1 more Smart Citation